Freeze-Fracture Replica Immunolabelling Reveals Urothelial Plaques in Cultured Urothelial Cells - Kreft, Mateja Erdani; Robenek, Horst (PLOS ONE, 2012)
The primary function of the urothelium is to provide the tightest and most impermeable barrier in the body, i.e. the blood-urine barrier. Urothelial plaques are formed and inserted into the apical plasma membrane during advanced stages of urothelial cell differentiation. Currently, it is supposed that differentiation with the final formation of urothelial plaques is hindered in cultured urothelial cells. With the aid of the high-resolution imaging technique of freeze-fracture replica immunolabelling, we here provide evidence that urothelial cells in vitro form uroplakin-positive urothelial plaques, localized in fusiform-shaped vesicles and apical plasma membranes. With the establishment of such an in vitro model of urothelial cells with fully developed urothelial plaques and functional properties equivalent to normal bladder urothelium, new perspectives have emerged which challenge prevailing concepts of apical plasma membrane biogenesis and blood-urine barrier development. This may hopefully provide a timely impulse for many ongoing studies and open up new questions for future research.